Cardiovascular and Gas Exchange Effects of Individualized Positive End-Expiratory Pressures in Cats Anesthetized With Isoflurane - Machado, Marcela L.; Soares, Joao H. N.; Pypendop, Bruno H.; Aguiar, Antonio J. A.; Braun, Christina; Motta-Ribeiro, Gabriel C.; Jandre, Frederico C. (Frontiers in Veterinary Science, 2022)
Objectives: To compare the effects of four levels of end expiratory pressure [zero (ZEEP) and three levels of positive end expiratory pressure (PEEP)] on the cardiovascular system and gas exchange of cats anesthetized with isoflurane and mechanically ventilated for three hours. Study design: Prospective, randomized, controlled trial Animals: Six healthy male cats Methods: Anesthesia was induced with isoflurane and maintained at 1.3 minimum alveolar concentration. PEEP of maximal respiratory compliance (PEEPmaxCrs) was identified, and cats were randomly ventilated for three hours with one of the following end-expiratory pressures: ZEEP, PEEPmaxCrs minus 2 cmH2O (PEEPmaxCrs-2), PEEPmaxCrs, and PEEPmaxCrs plus 2 cmH2O (PEEPmaxCrs+2). Cardiovascular and gas exchange variables were recorded at 5, 30, 60, 120 and 180 minutes (T5 to T180, respectively) of ventilation and compared between and within ventilation treatments with mixed-model ANOVA followed by Dunnet’s and Tukey’s tests or Friedman test followed by the Dunn’s tests. Significance was considered p < 0.05. Results: Mean arterial pressure (MAP - mmHg) was lower in PEEPmaxCrs+2 [63 (49 – 69); median (range)] when compared to ZEEP [71 (67 – 113)] at T5 and stroke index (mL/beat/kg) was lower in PEEPmaxCrs+2 (0.70 ± 0.20; mean ± SD) than ZEEP (0.90 ± 0.20) at T60. Cardiac index, oxygen delivery index (DO2I), systemic vascular resistance index and shunt fraction were not significantly different between treatments. The ratio between arterial partial pressure and inspired concentration of oxygen (PaO2/FIO2) was lower in ZEEP than in all PEEP treatments at various timepoints. At T180, DO2I was higher when compared to T5 in PEEPmaxCrs. Dopamine was required to maintain MAP higher than 60 mmHg in one cat during PEEPmaxCrs and in three cats during PEEPmaxCrs+2. Conclusion: In isoflurane-anesthetized cats, all levels of PEEP mildly improved gas exchange with no difference in DO2I when compared to ZEEP. PEEP levels higher than PEEPmaxCrs-2 caused more cardiovascular depression and dopamine was an effective treatment. A temporal increase in DO2I was observed in the cats ventilated with PEEPmaxCrs. The effects of these levels of PEEP on respiratory mechanics, ventilation-induced-lung-injury, as well as in obese and critically ill cats deserve future investigation.